2012
DOI: 10.1007/s11284-012-0957-1
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the invasion history of coral berry Ardisia crenata from China to the USA using molecular markers

Abstract: Genetic comparisons between native and invasive populations of a species can provide insights into its invasion history information, which is useful for guiding management and control strategies. The coral berry Ardisia crenata was introduced to Florida last century as a cultivated ornament plant, and has since spread widely throughout the southern regions of the USA. Previously, the genetic variation among 20 natural populations of A. crenata across its distribution center in southern China was quantified usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Surprisingly, several plastome markers commonly used for molecular phylogenetics of asterids at low taxonomic levels, such as regions between trnT - UGU and trnF - GAA [20], [28], [62], [63] and between atpB and rbcL [63], [64], [65], are not included in this list. To resolve interspecific relationships in a speciose genus such as Ardisia , suitable markers should be variable and, at the same time, encompass a region of adequate length, so that there will be sufficient characters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, several plastome markers commonly used for molecular phylogenetics of asterids at low taxonomic levels, such as regions between trnT - UGU and trnF - GAA [20], [28], [62], [63] and between atpB and rbcL [63], [64], [65], are not included in this list. To resolve interspecific relationships in a speciose genus such as Ardisia , suitable markers should be variable and, at the same time, encompass a region of adequate length, so that there will be sufficient characters.…”
Section: Resultsmentioning
confidence: 99%
“…crenata has the longest history of cultivation – nearly 200 years since its first description as an ornamental [19]. It also has attracted great attention for being an invasive species in the USA [20]. The species chosen in this study, A .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of any simulations looking at the effect of null alleles on InStruct sample assignment. However, sample assignment by STRUCTURE is robust to null alleles (Carlsson 2008) and other studies have found very similar results between the programs (Gunn et al 2011;Tatarenkov et al 2007), even when there is some evidence of null alleles (Niu et al 2012). For both analyses, the actual number of population clusters that best fit the data was calculated using the Dk method of Evanno et al (2005) in STRUCTURE Harvester (Earl and vonHoldt 2012) or by hand using the likelihood values.…”
Section: Analysis Of Microsatellite Datamentioning
confidence: 97%
“…Hen's eyes (Ardisia crenata Sims), also known as coral ardisia, was introduced into Florida as an ornamental shrub in the early 1900s (Dozier 1999;Hutchinson et al 2011;Niu et al 2012;Sellers et al 2007). There are more than 500 species within the genus Ardisia that are native to tropical and subtropical regions of eastern Asia, where some are ornamental or used for food and medicine (Hutchinson et al 2011;Kobayashi and de Mejía 2005).…”
Section: Introductionmentioning
confidence: 99%